THE EFFECT OF FE-OXIDIZING BACTERIA ON FE-SILICATE MINERAL DISSOLUTION - Santelli C.M.; Welch S.A.; Westrich H.R.; Banfield J.F. (My University, 2001)
Acidithiobacillus ferrooxidans are commonly present in acid mine drainage (AMD). A. ferrooxidans derive metabolic energy from oxidation of Fe2+ present in natural acid solutions and also may be able to utilize Fe2+ released by dissolution of silicate minerals during acid neutralization reactions. Natural and synthetic fayalites were reacted in solutions with initial pH values of 2.0, 3.0 and 4.0 in the presence of A. ferrooxidans and in abiotic solutions in order to determine whether these chemolithotrophic bacteria can be sustained by acid-promoted fayalite dissolution and to measure the impact of their metabolism on acid neutralization rates. The production of almost the maximum Fe3+ from the available Fe in solution in microbial experiments (compared to no production of Fe3+ in abiotic controls) confirms A. ferrooxidans metabolism. Furthermore, cell division was detected and the total cell numbers increased over the duration of experiments. Thus, over the pH range 2-4, fayalite dissolution can sustain growth of A. ferrooxidans. However, ferric iron released by A. ferrooxidans metabolism dramatically inhibited dissolution rates by 50-98% compared to the abiotic controls.Two sets of abiotic experiments were conducted to determine why microbial iron oxidation suppressed fayalite dissolution. Firstly, fayalite was dissolved at pH 2 in fully oxygenated and anoxic solutions. No significant difference was observed between rates in these experiments, as expected, due to extremely slow inorganic ferrous iron oxidation rates at pH 2. Experiments were also carried out to determine the effects of the concentrations of Fe2+, Mg2+ and Fe3+ on fayalite dissolution. Neither Fe2+ nor Mg2+ had an effect on the dissolution reaction. However, Fe3+, in the solution, inhibited both silica and iron release in the control, very similar to the biologically mediated fayalite dissolution reaction. Because ferric iron produced in microbial experiments was partitioned into nanocrystalline goethite (with very low Si) that was loosely associated with fayalite surfaces or coated the A. ferrooxidans cells, the decreased rates of accumulation of Fe and Si in solution cannot be attributed to diffusion inhibition by goethite or to precipitation of Fe-Si-rich minerals. The magnitude of the effect of Fe3+ addition (or enzymatic iron oxidation) on fayalite dissolution rates, especially at low extents of fayalite reaction, is most consistent with suppression of dissolution by interaction between Fe3+ and surface sites. These results suggest that microorganisms can significantly reduce the rate at which silicate hydrolysis reactions can neutralize acidic solutions in the environment.
Keywords: FE-OXIDIZING BACTERIA; FE-SILICATE MINERAL DISSOLUTION; THIOBACILLUS FERROOXIDANS